I Love Indonesia: A Junior Encyclopedia for Early Childhood Education to Promote Local Culture Using Ethnopedagogy - Roudlotun Ni'mah; Endang Puspitasari; Siti Labiba Kusna (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
The rise device technology, making civilization the more faded, culture foreigners who enter without filter, start to displace culture local impact in education child age early, then required a medium for stimulate knowledge child about culture local around. Types of research This is research and development or Research and Development (R&D). Development model This ADDIE with steps development consists of on stages analyze, design, development, implementation, and evaluation. Study This aiming produce Encyclopedia child as source Study through approach ethnopedagogic. Research This conducted at the Residency Bojonegoro. Subject study is a teacher and child of group B of Mardiwiyata 2 Kindergarten, Tuban , RA Madinatul Ulum Bojonegoro, and ABA Kindergarten, Guno Lamongan For know practicality and effectiveness Junior encyclopedia. Based on results study obtained that Encyclopedia child Based on local residency culture bojonegoro developed own specifications with Kiritera quality (standard) of non- text books, and has fulfil criteria validity with score (4.56), criteria practicality with score teacher response (4.33) and response students (4.21), and Effectiveness with (84%), so that the Junior Encyclopedia media is based on local residency culture bojonegoro can used as Source Study.